2014
DOI: 10.1088/0004-637x/788/1/7
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Nonlocality of the Small-Scale Solar Dynamo

Abstract: We explore the nature of the small-scale solar dynamo by tracking magnetic features. We investigate two previously explored categories of the small-scale solar dynamo: shallow and deep. Recent modeling work on the shallow dynamo has produced a number of scenarios for how a strong network concentration can influence the formation and polarity of nearby small-scale magnetic features. These scenarios have measurable signatures, for which we test using magnetograms from the Narrowband Filter Imager (NFI) on board … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Observations suggest that small-scale magnetic field in the solar photosphere is mostly independent from the strength of nearby network field (Ishikawa & Tsuneta 2009;Lites 2011;Lamb et al 2014) as well as independent of the solar cycle (Buehler et al 2013;Lites et al 2014). This supports the view that the origin of small-scale magnetism is due to a small-scale dynamo that operates independently from the large-scale dynamo responsible for the solar cycle.…”
Section: Introductionmentioning
confidence: 99%
“…Observations suggest that small-scale magnetic field in the solar photosphere is mostly independent from the strength of nearby network field (Ishikawa & Tsuneta 2009;Lites 2011;Lamb et al 2014) as well as independent of the solar cycle (Buehler et al 2013;Lites et al 2014). This supports the view that the origin of small-scale magnetism is due to a small-scale dynamo that operates independently from the large-scale dynamo responsible for the solar cycle.…”
Section: Introductionmentioning
confidence: 99%
“…The origin of bipoles with total fluxes 10 20 Mx, including in particular ERs, is often attributed to a poorly understood small-scale dynamo, in which turbulent convection acts to shred the larger-scale fields originating from the main, rotationally driven dynamo associated with sunspots and ARs (see, e.g., Cattaneo, 1999;Cattaneo, Emonet, and Weiss, 2003;Guglielmino et al, 2012). Based on the lack of correlation between the spatial distributions of network concentrations and small-scale fields, Lamb, Howard, and DeForest (2014) suggested that the stretching and shredding occur deep in the convection zone rather than near the solar surface. To our knowledge, however, none of the existing models predicts the emergence of small-scale fields within AR plages.…”
Section: Nature Of the Footpoint Fine Structure: Ephemeral Regions Gr...mentioning
confidence: 99%
“…While this is sufficient to seed solar dynamo and surface flux transport models, as well as to characterize the large scale statistical properties of BMRs and their dependence of solar activity, there is immense value in building catalogs that take advantage of full instrumental cadence and scale. The reason is that such a catalog will enable a wide array of statistical analyses that can shed light in the scaling and origin of surface magnetism [7]- [10], the nature of observable dynamo action [10], [11], dependence of surface magnetism on solar activity [12], [13], and characterization of the solar extended cycle [14], [15], among many other examples.…”
Section: Future Work: Building a Multi-scale Magnetic Catalog Using B...mentioning
confidence: 99%
“…Starting development in 2001, SWAMIS [16] has evolved to be a truly multi-scale detection algorithm that has been used to study flux balance in solar surface magnetism [17], [18], flux distribution of magnetic elements [9], dissipation of surface magnetic elements [19], and locality of surface dynamo action [11].…”
Section: A Swamis: a Multi-scale Feature Tracking Algorithmmentioning
confidence: 99%